Bladder Paraganglioma: A Comprehensive Review on an Uncommon Bladder Tumour Mimicker - Ivan Thia (Current Progress in Medicine and Medical Research Vol. 9, 2023)
Bladder paragangliomas are rare and unpredictable tumours with malignant potential. They tend to be associated with hereditary disorders and manifest symptoms at some point. Secreting sympathetic tumours can be triggered by changes in detrusor pressure and cause systemic effects. Diagnosis of bladder paragangliomas is challenging, given the variable presenting symptoms and requires a high index of suspicion. Incorrect diagnosis can result in anaesthetic complications during resection. Gold standard treatment involves removal of the paraganglioma in its entirety, especially for symptomatic, secreting sympathetic paragangliomas as these are at highest risk of metastases. This chapter discusses bladder paraganglioma in depth, including its aetiology, presentation, diagnosis and management and aims to provide a comprehensive review of this rare condition.